Self-compassion, well-being, and body image concern in young Japanese women: The role of positive and negative facets of self-compassion - Eriko Takahashi; Ryotaro Fukuda; Takumi Takahashi; Taisuke Katsuragawa (PLoS ONE, 2025)
The present study comprised two studies to examine how decreasing the negative facet of self-compassion, in addition to increasing its positive facet, is associated with body image and well-being in young Japanese women. Study 1 employed cross-sectional structural equation modeling using survey methodology to test hypothetical models. Participants (N = 577, mean age = 25.1 years, SD = 5.1) were recruited from an online community. A comparison of self-compassion models indicated that both one-factor and two-factor structures were valid, with the one-factor model and the negative component of the two-factor model significantly predicting well-being and appearance schemas, which in turn predicted body image concerns and abnormal eating behaviors. While these findings support the study’s hypothesized model and align with the cognitive-behavioral model of body image, the positive component showed only weak and maladaptive associations with body image variables, contrasting with prior intervention studies that reported beneficial effects. Study 2 was a parallel-group randomized controlled trial with 158 women randomly assigned to one of three groups: (1) decreased negative facet of self-compassion (DN; N = 48), (2) DN combined with increased positive facet (N = 53), or (3) non-intervention control (N = 57). After an image task to induce body dissatisfaction, participants completed measures of body dissatisfaction, self-esteem, and emotions before and after the self-compassion micro-intervention. The combined intervention significantly reduced body dissatisfaction and improved self-esteem compared to the control group. However, no significant difference was found between the DN-only and combined intervention groups. These findings suggest that the positive and negative facets of self-compassion have distinct effects on body image, well-being, and related outcomes. Further research is needed to clarify the mechanisms through which interventions that both reduce negative and enhance positive facets of self-compassion improve body image and emotional well-being.